If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 + -7x = 20x + 15 Reorder the terms: 78 + -7x = 15 + 20x Solving 78 + -7x = 15 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 78 + -7x + -20x = 15 + 20x + -20x Combine like terms: -7x + -20x = -27x 78 + -27x = 15 + 20x + -20x Combine like terms: 20x + -20x = 0 78 + -27x = 15 + 0 78 + -27x = 15 Add '-78' to each side of the equation. 78 + -78 + -27x = 15 + -78 Combine like terms: 78 + -78 = 0 0 + -27x = 15 + -78 -27x = 15 + -78 Combine like terms: 15 + -78 = -63 -27x = -63 Divide each side by '-27'. x = 2.333333333 Simplifying x = 2.333333333
| -9=r | | -(7x-4)+4x-5=-1 | | 6-10x=39-17x | | -144=-12x | | -(6x-4)+4x-6=-2 | | 11.4(x+3)+2=4.5(x+1) | | 5n-2n=-9 | | -12*12= | | 2.625=fraction | | 5=5+2m+3m | | 12*-12= | | 7(-16)(0)(-3)= | | Y=-25+4(x+5) | | x+x+4+3(x)+7=71 | | 1x+8=8x+22 | | 9x=3y-6 | | 13x+5=1x+11 | | 0.5a+2=5 | | 9x+15=3x+17 | | Y=10+3(x-5) | | x+x+4+3timesx+7=71 | | -3+x=-38 | | 2x+8=1x+3 | | 2x+6+x=90 | | P=2(33)+2(20) | | -6x-23=36 | | -4+(-8)-16-(9)= | | -5x-12=15 | | Y=-13+4(x+2) | | 4-x=-2x-7 | | 2(2y-7)+2y=106 | | x=2(20)-7 |